Case report: Green nail syndrome in an epidemic prevention volunteer during the outbreak of the Omicron in Shanghai - Yu, Qian; Hu, Sheng; Li, Wei; Yang, Lianjuan (Frontiers in Public Health, 2022)
Green nail syndrome (GNS) is an infectious disorder characterized by greenish discoloration of the nail plate. Pseudomonas aeruginosa is the most common organism that causes GNS. It is an opportunistic human pathogen that preferentially colonizes moist environments, and thus, it usually affects patients with a history of prolonged exposure to moist environments. Here, we describe a case of GNS in an epidemic prevention volunteer that was caused by wearing personal protective equipment for prolonged durations. The case was reported during the outbreak caused by the SARS-CoV-2 Omicron variant in Shanghai. After receiving information about his condition and proper treatment, the patient was cured.